Public Knowledge, Attitudes, and Willingness to Use Genetically Modified Foods in Ogun State, Nigeria - Olusegun Emmanuel Ogundele; Folasade Tinuade Ojo; Adebola Daniel Awofodu (Genetics & Applications)
The increasing focus on genetically modified (GM) foods has sparked significant debate, particularly in developing countries like Nigeria, where food security remains a pressing issue. This study aims to assess public knowledge, attitudes, and willingness to use GM foods in Ogun State, Nigeria, in light of the federal government's endorsement of some GM crops to enhance agricultural productivity and nutritional quality. A descriptive survey design was employed, targeting adults aged 18 years and above across four divisions of Ogun State: Ijebu, Egba, Remo, and Yewa. A total of 1,104 participants were selected using stratified random sampling. Data were collected through a structured questionnaire designed to evaluate knowledge, attitudes, and willingness regarding GM foods. The findings indicate that 70.9% of respondents had heard of GM foods, but only 39% accurately distinguished them from hybrids. Willingness to purchase GM foods was high, particularly among those who perceived them as healthier or more affordable. Regional differences were observed, with participants from Remo exhibiting the highest acceptance levels. Concerns regarding health risks and environmental impacts were prevalent, highlighting the need for targeted educational initiatives to address misconceptions and improve public understanding. This study provides insights into the perceptions of GM foods in Ogun State, emphasising the importance of education in fostering acceptance. It appears that while there is general willingness to adopt GM foods, significant knowledge gaps and persistent misconceptions must be addressed to facilitate informed decision-making and support the integration of GM technologies into sustainable agricultural practices.